Adaptations to six months of aerobic swim training: Changes in velocity, stroke rate, stroke length and blood lactate - Wakayoshi, K.; Yoshida, T.; Ikuta, Y.; Mutoh, Y.; Miyashita, M. (International Journal of Sports Medicine, 1993)
This study evaluated how stroke length, stroke rate, stroke velocity, and blood lactate changed as a result of six months of aerobic training. Ss were trained male college swimmers. A variety of tests were performed to assess the dependent variables prior to and after the six-month period of mainly (90%) aerobic training (8,000 m daily x 8 times per week). The following were found when pre- and post-intervention measures were compared. Swimming velocity improved in six of seven Ss due to increases in stroke length. Lactate level after a maximum effort swim was lower. Blood lactate concentration decreased relative to swimming velocity. Stroke rate did not change. Stroke length was maintained or increased during the last 100 m of a 400 m maximal test. Implication: Aerobic swimming training improved performance factors that would be expected to improve from that type of stimulation. It is not surprising that stroke length improved over other factors since stroke rates are individually optimized and preferred, aerobic training stimulates swimming efficiency, and aerobic training also slightly suppresses the development of lactate after maximal performances. That changes occurred after six months of training was not unexpected for if none had been evidenced, the nature of the training stimulus would have been questionable.